Innovation of marine tourism development in the east coast of North Sumatra Province - Indra Utama; Syarifuddin Siba; Nobrya Husni; Anton Parlindungan Sinaga; Silvia Darina; deni syahputra; Martina Silaban; Yanita Yanita (Inovasi, 2022)
The tourism potential in the northern part of the east coast of North Sumatra is still not widely exposed. In addition, the competitiveness of tourism in North Sumatra is still relatively low as the third largest province in Indonesia. This study aims to analyze marine tourism objects and their development innovations. The research method used is observational through surveys and qualitative descriptive analysis techniques. Collecting data using survey methods, interviews, and document searches. Tourism potential data is obtained through surveys, interviews and document searches. The tourist objects analyzed were: Medan City (Sihombak Lake Tourism Park, China City Museum, Labuhan Old Town Site, and Sicanang Mangrove Tourism); Deli Serdang Regency (Tanjung Rejo mangrove tourism and Siba Island); and, Langkat Regency (the tourist village of Jaring Halus and the Selotong eagle breeding). Based on the results of the analysis of the elements of attraction of marine tourism objects, elements that require strengthening, namely: attraction; marketing; market potential; visitor settings; and, climate. Innovation for the development of marine tourism objects in the northern part of the east coast of North Sumatra is carried out by involving innovation actors in strengthening the supporting elements, namely: attraction; marketing; market potential; visitor settings; and, climate. The innovation actors who play a role consist of: government, business, academia, and society. Keyword: marine tourism; east coast; innovation; North Sumatra